Architecture speaks: A music school for the deaf - Warman, Craig Barry (My University, 2013)
How are the sensory impaired included within design globally, today? The spaces we design as architects seem to lack the inclusion of all the senses. Either this is the case, or we as users forget to listen, touch, taste and smell these spaces created. It is intended to incorporate the use of all the senses within architectural design and allow for the sensory impaired to experience architecture in a similar way the sensory able do. The key link to understanding these issues, is through phenomenology. Phenomenology argues the bias of vision and the exclusion or underplaying of the remaining senses; the argument here is it lacks the inclusion of the sensory impaired. It is found that through vision one is able to “experience” sound, it is through the means of visualisations and vibrations that the inclusion of the Deaf would take place. It is important to heighten the remaining senses to the level of the dominant (vision); thus elevating all users experiences through architecture.